Cu-alpha-MnO2 nanowire and preparation method thereof, water-based zinc ion battery positive plate and preparation method thereof, and water-based zinc ion battery
Patent Information
- Application Number
- CN202611270846.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明的目的是为了克服现有二氧化锰基正极材料用于水系锌离子电池时,普遍存在本征导电性差、锌离子反复嵌脱易引发晶格坍塌、锰离子溶解流失,以及离子扩散动力学缓慢、高倍率性能与循环稳定性不足的问题,提供一种结构稳定、离子传输高效、倍率与循环性能优异的Cu-α-MnO2纳米线正极材料
[0012]针对现有二氧化锰基正极材料用于水系锌离子电池时,普遍存在本征导电性差、锌离子反复嵌脱易引发晶格坍塌、锰离子溶解流失,以及离子扩散动力学缓慢、高倍率性能与循环稳定性不足等技术缺陷,常规复合方式还存在铜组分分散不均、界面结合较弱、易发生金属溶出等问题。
Smart Images

Figure CN122916218A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy battery technology, specifically to a Cu-α-MnO2 nanowire and its preparation method, an aqueous zinc-ion battery cathode sheet and its preparation method, and an aqueous zinc-ion battery. Background Technology
[0002] Currently, aqueous zinc-ion batteries are considered a strong candidate for future large-scale energy storage systems due to their inherent safety, low cost, and environmental friendliness. Manganese dioxide (MnO2) is a highly promising cathode material due to its high theoretical capacity, suitable voltage platform, and abundant reserves. However, pure-phase MnO2 suffers from problems such as crystal structure instability, manganese dissolution, and Jahn-Teller distortion during charge and discharge, making it difficult to meet practical application requirements in terms of cycle life and rate performance.
[0003] To address these shortcomings, researchers have introduced ion doping strategies, particularly rare-earth element doping, to stabilize crystal structures and suppress phase transitions. For example, existing technologies (such as CN113451505A) have attempted to incorporate La... 3+ Gd 3+ Rare earth ions are introduced into the MnO2 lattice. Due to their large ionic radius and unique 4f electron layer structure, these dopant ions can theoretically broaden the layered tunnel structure of MnO2, enhance structural stability, and improve its electronic conductivity.
[0004] However, this existing technology has the following significant shortcomings: First, under conventional synthesis conditions, the solid solubility in the MnO2 host lattice is usually low and unevenly distributed, easily segregating at grain boundaries or surfaces to form an inactive second phase, failing to fully utilize the bulk phase modification effect of the dopant. Second, due to poor doping uniformity, the crystal structure of the resulting composite material remains unstable during deep zinc ion insertion / extraction, and the improvement in manganese dissolution and structural collapse after long-term cycling is limited.
[0005] Therefore, developing a novel Cu-MnO2 composite material with high solid solubility, uniform doping, and fundamentally improved material structural stability and electrochemical kinetic performance, as well as its efficient preparation method, has become an urgent technical problem to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems that existing manganese dioxide-based cathode materials generally suffer from when used in aqueous zinc-ion batteries, such as poor intrinsic conductivity, lattice collapse caused by repeated zinc ion insertion and extraction, manganese ion dissolution and loss, slow ion diffusion kinetics, and insufficient high-rate performance and cycle stability. The invention provides a Cu-α-MnO2 nanowire cathode material with stable structure, high ion transport efficiency, and excellent rate and cycle performance.
[0007] To achieve the above objectives, a first aspect of the present invention provides a method for preparing Cu-α-MnO2 nanowires for use as positive electrodes in aqueous zinc-ion batteries, the method comprising: (1) In the presence of an inorganic solvent, copper sulfate and manganese sulfate are mixed to obtain mixture I; (2) The potassium permanganate solution is mixed with the mixture I for the second time to obtain product I; the amount of copper sulfate is 4-20 mol% based on the total amount of manganese sulfate and potassium permanganate solution on a dry basis. (3) The product I is subjected to a hydrothermal reaction to obtain product II; (4) The product II is dried to obtain the Cu-α-MnO2 nanowires.
[0008] A second aspect of the present invention provides Cu-α-MnO2 nanowires prepared by the method described in the first aspect.
[0009] A third aspect of the present invention provides a method for preparing a positive electrode sheet for an aqueous zinc-ion battery, the method comprising: S1: In the presence of an organic solvent, the binder, Cu-α-MnO2 nanowires, and conductive carbon black are brought into contact to obtain material I; S2: The material I is coated onto at least one surface of a titanium foil, and then dried and sliced sequentially to obtain a positive electrode sheet; The Cu-α-MnO2 nanowires are the Cu-α-MnO2 nanowires described in the second aspect.
[0010] A fourth aspect of the present invention provides an aqueous zinc-ion battery cathode sheet prepared by the method described in the third aspect.
[0011] A fifth aspect of the present invention provides an aqueous zinc-ion battery comprising the aqueous zinc-ion battery positive electrode sheet described in the fourth aspect.
[0012] When existing manganese dioxide-based cathode materials are used in aqueous zinc-ion batteries, they generally suffer from poor intrinsic conductivity, lattice collapse caused by repeated zinc ion insertion and extraction, manganese ion dissolution and loss, slow ion diffusion kinetics, and insufficient high-rate performance and cycle stability. Conventional composite methods also have problems such as uneven dispersion of copper components, weak interfacial bonding, and easy metal dissolution.
[0013] This invention provides a Cu-α-MnO2 nanowire cathode material with stable structure, high ion transport efficiency, and excellent rate and cycle performance. By precisely constructing heterogeneous interfaces and conductive networks, uniform dispersion of the copper component is achieved, effectively buffering the volume stress caused by zinc ion intercalation / deintercalation, suppressing manganese dissolution, and broadening the ion transport channels.
[0014] Furthermore, the preparation process of this Cu-α-MnO2 nanowire cathode material is simple, highly controllable, and can be prepared on a large scale. The microstructure can be optimized and the interfacial compatibility can be improved by controlling the reaction conditions.
[0015] In summary, this invention significantly improves the discharge capacity, rate performance, and long-cycle stability of aqueous zinc-ion batteries, promoting their practical application in large-scale energy storage. Attached Figure Description
[0016] Figure 1 This is a scanning electron microscope image of the Cu-α-MnO2 nanowires prepared in Example 1; Figure 2 This is the elemental mapping analysis diagram of the Cu-α-MnO2 nanowires prepared in Example 1; Figure 3 This is the X-ray diffraction pattern of the Cu-α-MnO2 nanowires prepared in Example 1; Figure 4 This is the X-ray photoelectron spectrum of the Cu-α-MnO2 nanowires prepared in Example 1; Figure 5 This is the Raman spectrum of the Cu-α-MnO2 nanowires prepared in Example 1; Figure 6 This is a thermogravimetric analysis (TGA) diagram of the Cu-α-MnO2 nanowires prepared in Example 1; Figure 7 The cyclic voltammetry curves of the Cu-α-MnO2 nanowires prepared in Example 1 are shown. Figure 8 The electrochemical impedance spectroscopy of the aqueous zinc-ion battery prepared in Example 1 is shown. Figure 9 The graph shows the cycle performance of the aqueous zinc-ion battery prepared in Example 1. Figure 10 This is a rate performance diagram of the aqueous zinc-ion battery prepared in Example 1; Figure 11 This is the constant current intermittent titration curve of the aqueous zinc-ion battery prepared in Example 1. Detailed Implementation
[0017] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0018] As previously described, a first aspect of the present invention provides a method for preparing Cu-α-MnO2 nanowires for use as positive electrodes in aqueous zinc-ion batteries, the method comprising: (1) In the presence of an inorganic solvent, copper sulfate and manganese sulfate are mixed to obtain mixture I; (2) The potassium permanganate solution is mixed with the mixture I for the second time to obtain product I; the amount of copper sulfate is 4-20 mol% based on the total amount of manganese sulfate and potassium permanganate solution on a dry basis. (3) The product I is subjected to a hydrothermal reaction to obtain product II; (4) The product II is dried to obtain the Cu-α-MnO2 nanowires.
[0019] Preferably, the amount of copper sulfate is 4-10 mol%, based on the total amount of manganese sulfate and potassium permanganate solution on a dry basis. The inventors have found that, under this preferred condition, the charge transfer rate of the Cu@α-MnO2 nanowires is faster, which can further improve conductivity.
[0020] Preferably, in step (1), the inorganic solvent is deionized water, and the amount of the inorganic solvent is controlled so that the concentration of copper sulfate is 0.01-0.06 mol / L.
[0021] Preferably, in step (2), the molar concentration of the potassium permanganate solution is 0.1-0.5 mol / L. This invention does not impose any special requirements on the preparation method of the potassium permanganate solution; those skilled in the art can use known techniques in the field.
[0022] Preferably, the molar ratio of manganese sulfate to potassium permanganate solution is 1-2:1.
[0023] Preferably, in step (2), the conditions for the second mixing include: a stirring speed of 500-600 rpm, a time of 10-30 min, and a temperature of 20-40°C. The present invention does not impose special requirements on the stirring device; for example, a magnetic stirrer can be used.
[0024] Preferably, in step (3), the conditions for the hydrothermal reaction include: a temperature of 130-200℃ and a time of 2-6h.
[0025] More preferably, in step (3), the conditions for the hydrothermal reaction include: a temperature of 140-160°C and a time of 3-5 hours.
[0026] Preferably, in step (4), the drying process is carried out at a temperature of 80-90°C for 0.5-3 hours.
[0027] In a preferred embodiment, in step (4), before performing the drying process, product II is first filtered and washed sequentially, and then the drying process is performed. The present invention does not impose special requirements on the filtration and washing conditions; those skilled in the art can use known techniques in the field. These requirements will not be elaborated upon here, and should not be construed as limitations on the present invention.
[0028] Preferably, the method further includes: in step (4), grinding the material obtained after the drying process to obtain the Cu-α-MnO2 nanowires.
[0029] More preferably, the conditions of the grinding process are controlled so that the length of the Cu-α-MnO2 nanowires is 200-400 nm and the diameter is 20-30 nm.
[0030] More preferably, in step (4), the grinding process takes 2-6 hours.
[0031] More preferably, in step (4), the grinding process is carried out in an agate mortar.
[0032] As previously stated, a second aspect of the present invention provides Cu-α-MnO2 nanowires prepared by the method described in the first aspect.
[0033] As previously described, a third aspect of the present invention provides a method for preparing a positive electrode sheet for an aqueous zinc-ion battery, the method comprising: S1: In the presence of an organic solvent, the binder, Cu-α-MnO2 nanowires, and conductive carbon black are brought into contact to obtain material I; S2: The material I is coated onto at least one surface of a titanium foil, and then dried and sliced sequentially to obtain a positive electrode sheet; The Cu-α-MnO2 nanowires are the Cu-α-MnO2 nanowires described in the second aspect.
[0034] Preferably, in step S1, the mass ratio of the Cu-α-MnO2 nanowires, the conductive carbon black, and the binder is 1:0.5-2:5-10.
[0035] Preferably, in step S1, the adhesive is selected from at least one of polyvinylidene fluoride, polyacrylic acid, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0036] Preferably, the amount of organic solvent used in step S1 is controlled so that the concentration of the adhesive in material I is 0.01-0.05 g / mL.
[0037] Preferably, in step S1, the organic solvent is selected from at least one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylformamide, and dimethylacetamide.
[0038] Preferably, in step S1, the contact is carried out under grinding conditions, and the grinding time is 0.5-2 hours.
[0039] Preferably, in step S2, the coating thickness is 100-300 μm, and the titanium foil thickness is 0.01-0.03 mm. The present invention does not place special requirements on the coating apparatus; exemplarily, a tetragonal coater can be used for coating.
[0040] Preferably, in step S2, the drying conditions include: a temperature of 80-90°C and a time of 0.5-3 hours. The present invention does not impose special requirements on the drying apparatus; for example, a forced-air drying oven can be used.
[0041] Preferably, in step S2, the slicing process includes slicing using a battery punching machine with a punching diameter of 10-15 mm.
[0042] As previously stated, a fourth aspect of the present invention provides an aqueous zinc-ion battery cathode sheet prepared by the method described in the third aspect.
[0043] As previously described, the fifth aspect of the present invention provides an aqueous zinc-ion battery containing the aqueous zinc-ion battery positive electrode sheet described in the fourth aspect.
[0044] Preferably, the aqueous zinc-ion battery also contains an electrolyte and a negative electrode.
[0045] Preferably, the electrolyte is a mixed solution of zinc sulfate and manganese sulfate.
[0046] Preferably, the concentration of zinc sulfate in the mixed solution is 1-3 mol / L.
[0047] More preferably, the concentration of manganese sulfate in the mixed solution is 0.01-0.5 mol / L.
[0048] More preferably, the negative electrode sheet is a zinc foil sheet with a diameter of 10-15 mm and a thickness of 0.01-0.05 mm.
[0049] Preferably, the method for preparing the aqueous zinc-ion battery includes: Aqueous zinc-ion batteries are obtained by assembling CR2032 aluminized battery casing, 304 stainless steel gasket, 316 stainless steel spring sheet, GF / D glass fiber separator, electrolyte, negative electrode sheet, and aqueous zinc-ion battery positive electrode sheet using a button battery sealing machine.
[0050] The present invention will be described in detail below through embodiments. Unless otherwise specified, all instruments and materials used in the following embodiments are commercially available products.
[0051] In the following examples, room temperature refers to a temperature of 25±2℃.
[0052] Copper sulfate: purity ≥98.5wt%, purchased from Greater Reagent Ltd., grade 01114878.
[0053] Copper nitrate: purity 98 wt%, purchased from Adamas Reagent Co., Ltd., grade 01038238.
[0054] Nickel sulfate hexahydrate: purity ≥98.5wt%, purchased from Greater Reagent Ltd., grade 01220661.
[0055] Manganese sulfate monohydrate: purity 99.0-101.0 wt%, purchased from Adamas Reagent Co., Ltd., grade 01000519.
[0056] Manganese chloride: purity 99 wt%, purchased from Adamas Reagent Co., Ltd., grade 011042074.
[0057] Potassium permanganate: purity 99.5 wt%, purchased from Shanghai Titan Technology Co., Ltd., grade 01114373.
[0058] Polyvinylidene fluoride powder: purity 99wt%, purchased from Adamas Reagent Co., Ltd.
[0059] N-Methylpyrrolidone: purity 99.9 wt%, purchased from Adamas Reagent Co., Ltd., brand number 01220775.
[0060] Conductive carbon black: purchased from Guangdong Zhuguang New Energy Technology Co., Ltd.
[0061] Zinc sulfate heptahydrate: purity 99.5 wt%, purchased from Adamas Reagent Co., Ltd., grade 01220497.
[0062] Zinc foil negative electrode sheet: purchased from Haiyuan Scientific Metal Company.
[0063] CHI760E electrochemical workstation: purchased from CH Instruments Co., USA.
[0064] Example 1: Preparation of Cu-α-MnO2 nanowires (1) At room temperature, 0.001 mol of copper sulfate and 0.006 mol of manganese sulfate monohydrate were added to 35 mL of deionized water (i.e., inorganic solvent), and the mixture was sonicated for 10 min at 180 W to obtain mixture I. (2) At room temperature, 0.004 mol of potassium permanganate was added to 35 mL of deionized water to dissolve it, and a potassium permanganate solution with a concentration of 0.114 mol / L was obtained. The potassium permanganate solution was then mixed with the mixture I obtained in step (1) under a magnetic stirrer to obtain product I. The conditions for the second mixing were: stirring speed of 500 rpm, temperature of 25°C, and time of 10 min. (3) Transfer product I obtained in step (2) to a hydrothermal reactor, and then place the hydrothermal reactor in an oven preheated to 150°C for hydrothermal reaction (150°C, 4h). After the reaction is completed, let it stand in the oven to cool to room temperature to obtain product II. (4) The product II obtained in step (3) was filtered and washed with deionized water three times in sequence, and then dried (90℃, 2h) and cooled to room temperature; the dried material was then ground in an agate mortar for 4h to obtain Cu-α-MnO2 nanowires, named NM-1.
[0065] Examples 2-4 The same process as in Example 1 was used, except that the types / amounts of raw materials and process parameters were different, as shown in Table 1.
[0066] Table 1
[0067] Comparative Example 1 This embodiment is carried out with reference to the method of Embodiment 1, except that in step (1), the molar amount of copper sulfate is 0.0003 mol; the molar amount of manganese sulfate monohydrate is 0.006 mol. The remaining steps were the same as in Example 1, and Cu-α-MnO2 nanowires were obtained, named NM-D1.
[0068] Comparative Example 2 This embodiment is carried out with reference to the method of Embodiment 1, except that in step (1), "copper sulfate" is replaced with an equimolar amount of "copper nitrate". The remaining steps were the same as in Example 1, and Cu-α-MnO2 nanowires were obtained, named NM-D2.
[0069] Comparative Example 3 This embodiment is carried out according to the method of Embodiment 1, except that in step (1), "copper sulfate" is replaced with an equimolar amount of "nickel sulfate hexahydrate". The remaining steps are the same as in Example 1, and are named NM-D3.
[0070] Comparative Example 4 This embodiment is carried out according to the method of Embodiment 1, except that in step (1), "manganese sulfate monohydrate" is replaced with an equimolar amount of "manganese chloride". The remaining steps were the same as in Example 1, and Cu-α-MnO2 nanowires were obtained, named NM-D4.
[0071] Preparation Example 1: Preparation of Aqueous Zinc-ion Batteries S1: Dissolve 0.8g of polyvinylidene fluoride (PVDF, i.e., adhesive) in 32mL of N-methylpyrrolidone (NMP, i.e., organic solvent), then add 0.1g of Cu-α-MnO2 nanowires (NM-1) and 0.1g of conductive carbon black, place them in a mortar and grind for 1h, mix evenly, and obtain material I; S2: Material I is coated onto one surface of titanium foil (0.02 mm thick) using a square coater to a thickness of 200 μm. Then, it is dried at 85°C for 1 hour using a forced-air drying oven. The foil is then sliced using a battery punching machine with a punching diameter of 14 mm to obtain the positive electrode sheet of the aqueous zinc-ion battery. S3: Assemble a CR2032 aluminum-plated battery casing, 304 stainless steel gasket, 316 stainless steel spring sheet, GF / D glass fiber separator, 140μL electrolyte (2mol / L zinc sulfate heptahydrate and 0.1mol / L manganese sulfate monohydrate), negative electrode sheet (zinc foil sheet with a diameter of 14mm and a thickness of 0.02mm), and aqueous zinc-ion battery positive electrode sheet using a button cell sealing machine to obtain an aqueous zinc-ion battery.
[0072] Preparation Examples 2-4, and Comparative Preparation Examples 1 to 4: The same procedure as in Example 1 was used, except that the type of Cu-α-MnO2 nanowires was different, as shown in Table 2.
[0073] Table 2
[0074] Test example: The performance of the aqueous zinc-ion batteries prepared in the above preparation examples and comparative preparation examples was tested, and the test results are shown in Table 3.
[0075] The charge transfer resistance was tested using electrochemical impedance spectroscopy (EIS) on a CHI 760E electrochemical workstation, with a frequency range of 100 kHz to 0.01 Hz and an amplitude of 5 mV.
[0076] The initial specific capacity was tested as follows: To evaluate the long-term cycling stability of the electrode material, the LAND battery testing system was used within a voltage window of 0.8-1.8 V (vs. Zn). 2+ Within the range of / Zn), at 0.1 C (1 C = 100 mAh·g) -1 The current density was used to perform constant current charge and discharge tests, and the initial discharge specific capacity was recorded.
[0077] The method for testing specific capacity after cycling is the same as the method for testing initial specific capacity, except that the specific capacity stabilized after 200 cycles is recorded.
[0078] The specific capacitance test method at 5C is the same as the initial specific capacitance test method, except that the current density needs to be gradually increased from 0.1C to 5C, and the specific capacitance at 5C current density is recorded.
[0079] Table 3
[0080] The morphology of the Cu-α-MnO2 nanowires prepared in Example 1 was characterized by transmission electron microscopy (TEM). Figure 1 This is a scanning electron microscope image of the Cu-α-MnO2 nanowires prepared in Example 1. The results show that Cu-α-MnO2 exhibits a clear one-dimensional nanowire morphology, with a length of approximately 200-400 nm and a uniform diameter distribution of about 20-30 nm. The nanowire surface is smooth, without obvious attached particles or agglomerates, indicating high material purity and no significant phase separation.
[0081] Figure 2This is an elemental mapping analysis of the Cu-α-MnO2 nanowires prepared in Example 1. Energy-dispersive X-ray spectroscopy (EDS) surface scan results show that the Mn (yellow) and O (blue) signals are uniformly and continuously distributed along the entire nanowire profile, without local enrichment or loss, confirming that the nanowire body is MnO2. The Cu signal is not a discrete bright spot or speckle, but completely overlaps spatially with the Mn and O signals, and the intensity distribution is uniform, strongly indicating that Cu has been uniformly doped into the MnO2 lattice. Clear lattice fringes are visible in the image, and the measured interplanar spacing is 0.166 nm. This interplanar spacing corresponds to the (211) crystal plane of tetragonal α-MnO2 and is highly consistent with the XRD results described later. The lattice fringes are continuous and straight, and no lattice breaks or amorphous regions were observed, indicating that Cu doping has not destroyed the main lattice structure of MnO2, but rather formed a good solid solution.
[0082] The Cu-α-MnO2 nanowires prepared in Example 1 were characterized by XRD. Figure 3 This is the X-ray diffraction pattern of the Cu-α-MnO2 nanowires prepared in Example 1. The results show that all diffraction peaks are well indexed to the standard card PDF #00-044-0141 for tetragonal α-MnO2. No characteristic diffraction peaks belonging to copper oxides such as CuO were observed across the entire spectrum. This directly proves that Cu did not form an independent crystalline phase, but successfully entered the MnO2 lattice.
[0083] Compared to the standard card, all diffraction peaks (especially the main peak (211)) showed a slight, systematic shift to a lower angle. According to Bragg's equation (2d sinθ = λ), this shift implies an increase in interplanar spacing (d value). This is because of the doped Cu. 2+ The ionic radius (0.73 Å) is larger than that of the substituted Mn. 4+ The small ionic radius (0.53 Å) causes lattice expansion, which matches the actual interplanar spacing results obtained by TEM. The diffraction peaks exhibit some broadening, a typical characteristic of nanomaterials; according to the Scherrer equation, smaller particle sizes result in wider peaks. Figure 1 The nanowires observed were of consistent size. Figure 3 The material was confirmed to be pure-phase α-MnO2, and Cu was confirmed through the key evidence of lattice expansion. 2+ It has successfully replaced Mn 4+ Lattice doping was achieved at specific sites.
[0084] The Cu-α-MnO2 nanowires prepared in Example 1 were characterized by X-ray photoelectron spectroscopy (XPS). Figure 4The image shows the X-ray photoelectron spectrum of the Cu-α-MnO2 nanowires prepared in Example 1. The results show that the full spectrum clearly displays the characteristic photoelectron peaks of Mn, O, and Cu, with no other impurity elements, confirming the chemical composition of the sample.
[0085] The fine spectrum of Cu 2p shows a distinct and strong satellite peak observed on the high binding energy side of the main peak, which is characteristic of Cu. 2+ The characteristic fingerprint peaks indicate that the doped Cu mainly exists in the +2 valence state on the material surface, which is consistent with its substitution of Mn. 4+ Valence state matching at the site. Through peak fitting, Mn 2p can be decomposed into two components: Mn 4+ Mn is the main component; 3+ It is a minor component. Maintaining charge balance, when Cu... 2+ Replace Mn 4+ At this time, it will cause some of the neighboring Mn 4+ Reduced to Mn 3+ Mn 3+ The presence of this is another strong piece of evidence for the successful doping of Cu.
[0086] The O 1s spectrum can be fitted with three peaks: 529.8 eV represents lattice oxygen, with the highest intensity, originating from oxygen in the MnO2 framework; 31.2 eV represents oxygen vacancies, with significant intensity. Its appearance is related to the charge imbalance caused by Cu doping, and oxygen vacancies are formed in the lattice to compensate for the charge; 532.5 eV represents surface adsorbed oxygen, usually originating from surface adsorbed water.
[0087] The Cu-α-MnO2 nanowires prepared in Example 1 were characterized by Raman spectroscopy. Figure 5 This is the Raman spectrum of the Cu-α-MnO2 nanowires prepared in Example 1. Figure 5 It can be seen that the spectrum is at 639.2 cm⁻¹ -1 A strong and sharp peak is observed at this point, which is attributed to the A of α-MnO2. g The vibrational mode corresponds to the symmetric stretching vibration of Mn-O-Mn along the MnO6 octahedral chain, which is a characteristic Raman peak of MnO2 materials. The A... g Characteristic peaks are typically located at 630-640 cm⁻¹ -1 The peak position of this sample falls within this range, indicating that its main structure is still α-MnO2, consistent with the XRD results. For pure and highly crystalline α-MnO2, this peak is typically located at approximately 635 cm⁻¹. -1 The sample in question measures 639.2 cm. -1 It happened to be ~4 cm -1 The blue shift. This is due to Cu. 2+Replace Mn 4+ Cu doping leads to lattice expansion, but the bond energy of Cu-O bonds is generally different from that of Mn-O bonds. The blue shift observed here indicates that Cu doping enhances the bonding force of Mn-O-Cu, or that local lattice contraction occurs, thereby increasing the vibrational frequency. The peak half-width increases slightly, and the shape becomes asymmetrical, indicating that Cu doping introduces lattice distortion and structural disorder, increasing phonon scattering.
[0088] The Cu-α-MnO2 nanowires prepared in Example 1 were characterized by simultaneous thermogravimetric-differential scanning calorimetry (TG-DSC). Figure 6 The thermogravimetric analysis (TGA) diagram of Cu-α-MnO2 nanowires prepared in Example 1 shows that the thermal decomposition of Cu-doped α-MnO2 nanowires goes through three stages: physical adsorption water desorption (endothermic, 3.58%), release of surface hydroxyl groups and defect oxygen (weakly endothermic, 4.57%), and α-MnO2→Mn2O3 phase transition (strongly exothermic, 10.03%), ultimately leaving 81.63% of the Mn2O3 / CuMn2O4 mixed phase.
[0089] The strong exothermic peak at ~500 °C in the DSC curve confirms the structural recombination nature of the phase transition. Its peak temperature is approximately 20-30 °C lower than that of pure MnO2, directly demonstrating that Cu doping reduces the structural thermal stability. The weak signal from the second-stage DSC, together with the oxygen vacancies detected by XPS, provides both thermodynamic and structural evidence for the Cu-induced charge compensation mechanism.
[0090] The aqueous zinc-ion battery prepared in Example 1 was subjected to electrochemical testing using cyclic voltammetry. Figure 7 The cyclic voltammetry curves of the Cu-α-MnO2 nanowires prepared in Example 1 are shown, illustrating the CV curves within a potential window of 0.7 V to 1.9 V.
[0091] from Figure 7 As can be observed, the CV curve exhibits a pair of distinct redox peaks, indicating that the electrode material primarily exhibits Faraday pseudocapacitive behavior rather than the rectangular characteristics of an ideal double-layer capacitor. During the negative scan, a reduction peak appears at approximately 0.7–0.9 V, corresponding to Mn. 4+ To Mn 3+ The reduction reaction is accompanied by the proton H + The embedded MnO2 tunnel structure forms the MnOOH mesophase; during the forward scan, a corresponding oxidation peak appears at approximately 1.5-1.6 V, representing Mn 3+ Re-oxidized to Mn 4+ And the extraction of protons from the crystal lattice.
[0092] The potential difference ΔEp between the two peaks is about 0.7 V, which is significantly greater than the theoretical value of an ideal reversible system, indicating that the redox process is a quasi-reversible system. This is mainly due to the combined effect of factors such as electrode polarization, ohmic drop, and ion diffusion resistance.
[0093] The current ratio of the oxidation peak to the reduction peak is close to 1:1, indicating that the reaction product has good reversibility and structural stability, and no significant irreversible side reactions occur.
[0094] Furthermore, the broad peak shape of the CV curve suggests that the electrode process is not only controlled by the surface but also has a significant diffusion control contribution, reflecting the typical characteristics of pseudocapacitive materials.
[0095] The two CV curves are basically the same in shape, and the peak potential and peak current are relatively similar, indicating that the electrode material has good electrochemical stability and repeatability during cycling, and no obvious structural degradation or active material shedding has occurred.
[0096] Overall, the CV curves confirmed that Cu-doped α-MnO2 nanowires possess significant electrochemical activity, and Mn 4+ / Mn 3+ Redox pairs contribute the majority of its capacity.
[0097] Figure 8 To prepare the electrochemical impedance spectroscopy (EIS) of the aqueous zinc-ion battery prepared in Example 1, the EIS diagram consists of two parts: a semicircle in the high-frequency region and a diagonal line in the low-frequency region, each corresponding to a different electrochemical process.
[0098] The semicircle in the high-to-mid-frequency range corresponds to the charge transfer process, and the diameter of the semicircle represents the charge transfer resistance R2, which is approximately 209 Ω. The phase angle exponent n of the CPE is typically between 0.8 and 0.9, reflecting the surface roughness, porosity, and non-uniformity of the active material distribution. These characteristics are highly consistent with the nanowire morphology and porous structure of Cu-doped α-MnO2 nanowires.
[0099] The magnitude of the charge transfer resistance R2 directly affects the rate of electrode reaction kinetics: the smaller R2, the faster the charge transfer rate at the electrode / electrolyte interface, and the higher the electrochemical activity. The sloping line in the low-frequency region represents the Warburg diffusion impedance W1, with a slope close to 45°, indicating that the electrode process is controlled by ion diffusion in the low-frequency region. The Warburg impedance corresponds to the electroactive ions (such as H+). + Mn 4+ or Zn 2+ The degree to which the slope of the solid-state diffusion process within the electrode bulk phase deviates from 45° reflects the complexity of the diffusion path and the influence of the electrode microstructure.
[0100] For Cu-doped α-MnO2 nanowires, the oxygen vacancies introduced by copper ion doping provide additional channels and active sites for ion diffusion, which helps to reduce diffusion resistance and improve rate performance.
[0101] The cycle performance and rate performance of the aqueous zinc-ion battery prepared in Example 1 were tested using a blue electric system, as well as by galvanostatic intermittent titration (GITT) to obtain... Figure 9 , Figure 10 , Figure 11 .
[0102] Figure 9 This is a cycling performance graph of the aqueous zinc-ion battery prepared in Example 1, showing the changes in specific capacity and coulombic efficiency during long-term cycling. This is a core characterization method for evaluating the cycle life and reversibility of electrode materials. The specific capacity of this material exhibits a rapid initial decrease followed by a slower decrease with increasing cycle number. The initial capacity reaches 646.7 mAh·g. -1 This value is far higher than the theoretical capacity of MnO2 (approximately 308 mAh·g). -1 The main mechanisms involved are multi-electron redox reactions, where Mn undergoes electron transfer reactions in MnO2-based materials, theoretically doubling the capacity. Cu doping also participates in redox reactions, further increasing the capacity. Additional capacity related to oxygen vacancies is also involved, as Cu doping introduces oxygen vacancies into the α-MnO2 lattice. These oxygen vacancies can serve as additional zinc ion storage sites, contributing to capacity through surface adsorption or interfacial zinc storage mechanisms. Surface pseudocapacitive effects are also present; the nanowire morphology provides a high specific surface area, and numerous surface and near-surface sites can undergo rapid pseudocapacitive reactions, contributing significant capacity even at low rates.
[0103] After 100 cycles, the specific capacity rapidly decreased to 100 mAh·g. -1 The readings around 50 mAh·g indicate that most of the active substances have been completely deactivated, but the specific capacity remained stable at 50 mAh·g for an extended period. -1 The value of around 100 indicates that although the remaining active materials contribute limited capacity, they can still work stably, indicating that the intrinsic electrochemical reversibility is still good, only the overall capacity contribution of the electrode has been greatly reduced.
[0104] In the initial cycling phase (cycles 1-5), the coulombic efficiency was approximately 85-90%, which is normal during SEI film formation. Subsequently, the coulombic efficiency rapidly increased to over 98% within about 10-20 cycles and stabilized between 99-100% in subsequent cycles, indicating that the electrochemical reaction of this material exhibits excellent reversibility, a stable electrode / electrolyte interface, and no significant side reactions. This is one of the most important advantages of this material.
[0105] Figure 10This is a rate performance graph of the aqueous zinc-ion battery prepared in Example 1, showing the specific capacity change of the aqueous zinc-ion battery at different current densities (rates). It is a core characterization for evaluating the power performance and rate tolerance of electrode materials. The rate test adopts a stepped test scheme that gradually increases and then returns to low rates, covering five rate levels: 0.1C, 0.5C, 1C, 2C, and 5C. Approximately five cycles are performed at each rate, and finally, the test returns to 0.1C for recovery. This allows for the simultaneous evaluation of the material's rate response capability and structural reversibility.
[0106] At an initial rate of 0.1C, the material exhibits a high specific capacity. The initial capacity for the first cycle is 752.6 mAh·g. -1 Similar to the results of cyclic measurements, the material exhibits rapid capacity decay within 5 cycles, indicating that even at the lowest rate, the material is not completely stable—a SEI film continues to form. When the rate is increased to 0.5C, the capacity decreases significantly, with a capacity retention of approximately 55-65% of the initial 0.1C capacity. This decrease primarily reflects limitations imposed by ion diffusion kinetics.
[0107] At an extremely high 5C rate, the capacity drops to approximately 10 mAh·g. -1 The value is around 0.1C, indicating that the material's structure degrades significantly at high rates. When the rate recovers from 5C to the initial 0.1C, the capacity rebounds to approximately 350-400 mAh·g. -1 The capacity recovery rate was approximately 50% of the initial 0.1C capacity, indicating that the material's structure did not suffer completely irreversible damage after high-rate impact, and most active sites remained accessible and functioning normally.
[0108] Figure 11 This is the galvanostatic intermittent titration (GITT) curve of the aqueous zinc-ion battery prepared in Example 1. In terms of overall shape, the GITT curve covers the full potential window from about 0.0 V to 2.5 V and includes both charging (from low potential to high potential) and discharging (from high potential to low potential) directions.
[0109] Based on the overall GITT curve, the electrochemical behavior of this material can be summarized into three key characteristics: First, the high symmetry of the charge and discharge directions proves that the electrode reaction has excellent thermodynamic reversibility; second, the sloping characteristic of the curve without long plateaus indicates that the energy storage mechanism is mainly contributed by solid solution reaction and surface pseudocapacitance; third, the small step height and rapid relaxation behavior in the mid-potential range prove that the material has excellent zinc ion diffusion kinetics and a large diffusion coefficient in the mid-potential range.
[0110] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing Cu-α-MnO2 nanowires for use as positive electrodes in aqueous zinc-ion batteries, characterized in that, The method includes: (1) In the presence of an inorganic solvent, copper sulfate and manganese sulfate are mixed to obtain mixture I; (2) The potassium permanganate solution is mixed with the mixture I for the second time to obtain product I; the amount of copper sulfate is 4-20 mol% based on the total amount of manganese sulfate and potassium permanganate solution on a dry basis. (3) The product I is subjected to a hydrothermal reaction to obtain product II; (4) The product II is dried to obtain the Cu-α-MnO2 nanowires.
2. The method according to claim 1, characterized in that, Based on the total amount of the manganese sulfate and the potassium permanganate solution (on a dry basis), the amount of copper sulfate is 4-10 mol%. And / or, in step (2), the molar concentration of the potassium permanganate solution is 0.1-0.5 mol / L; And / or, the molar ratio of the manganese sulfate to the potassium permanganate solution (calculated as potassium permanganate) is 1-2:
1.
3. The method according to claim 1 or 2, characterized in that, In step (2), the conditions for the second mixing include: a stirring speed of 500-600 rpm, a time of 10-30 min, and a temperature of 20-40℃; And / or, in step (3), the conditions for the hydrothermal reaction include: a temperature of 130-200°C and a time of 2-6 hours; And / or, in step (4), the drying process is carried out at a temperature of 80-90°C for a time of 0.5-3 hours.
4. The method according to claim 1 or 2, characterized in that, The method further includes: in step (4), grinding the material obtained after the drying process to obtain the Cu-α-MnO2 nanowires.
5. The method according to claim 4, characterized in that, The grinding conditions are controlled so that the length of the Cu-α-MnO2 nanowires is 200-400 nm and the diameter is 20-30 nm.
6. Cu-α-MnO2 nanowires prepared by the method according to any one of claims 1-5.
7. A method for preparing a positive electrode sheet for an aqueous zinc-ion battery, characterized in that, The method includes: S1: In the presence of an organic solvent, the binder, Cu-α-MnO2 nanowires, and conductive carbon black are brought into contact to obtain material I; S2: The material I is coated onto at least one surface of a titanium foil, and then dried and sliced sequentially to obtain a positive electrode sheet; The Cu-α-MnO2 nanowires are those described in claim 6.
8. The method according to claim 7, characterized in that, In step S1, the mass ratio of the Cu-α-MnO2 nanowires, the conductive carbon black, and the binder is 1:0.5-2:5-10. And / or, in step S1, the adhesive is selected from at least one of polyvinylidene fluoride, polyacrylic acid, sodium carboxymethyl cellulose, and styrene-butadiene rubber; And / or, control the amount of organic solvent used in step S1 so that the concentration of the binder in material I is 0.01-0.05 g / mL.
9. An aqueous zinc-ion battery cathode sheet prepared by the method described in claim 7 or 8.
10. An aqueous zinc-ion battery, characterized in that, The battery contains the aqueous zinc-ion battery positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Magnetic random access memory unit, memory and equipment
CN113451505A